Implementation of internal monitoring programs for workers occupationally exposed by 131I in nuclear medicine services in Brazil (Brazilian Journal of Radiation Sciences (BJRS), 2018)
In nuclear medicine services (NMS), workers routinely handle radionuclides for diagnostic and therapy. This practice represents a risk of incorporation by these radionuclides. The International Atomic Energy Agency (IAEA) recommends the implementation of an internal monitoring program on workers exposed to annual effective doses greater than 1 mSv, as for example, those who handle 131I for therapy in NMS. Currently, in Brazil, there are not enough available laboratories qualified to provide internal monitoring services to attend all possible demand of internal monitoring if it such regulation were applied by the Brazilian Nuclear Regulatory Board (CNEN). The objective of this work is to disseminate simple and inexpensive methods for in vivo routine thyroid monitoring of 131I using equipment available in the NMS. Devices available in two public hospitals located in the city of Rio de Janeiro were calibrated for use in occupational internal monitoring. The equipments evaluated in this work presented enough sensitivity for such application, being suitable to access intakes of 131I in the thyroid and able to estimate doses below 1 mSv.